A new method for teaching microprocessors course using emulation. Issue 3 (9th December 2014) - Qaralleh, Esam A.; Darabkh, Khalid A.
ABSTRACT Microprocessors course is a challenging course for both students and instructors. The challenge arises by the nature of this course which is a combination of assembly language and hardware interface. The assembly language develops the students' ability to program in a low level programming language utilizing the instruction set of the 8086 processor, understanding the addressing modes (pointer concept), and exploring the nature of different instructions along with their execution times, dependences, implicit addressing for certain instructions, as well as flow control concerning the flags. The hardware interface helps the students in connecting various system components to build up a working system. Memory and input/output communications (read/write) operations are explained using timing diagrams and handshaking signals. In this paper, the aforementioned contents are addressed through developing an interesting project that is capable of integrating both hardware and software in an attractive environment characterized by being simple and inexpensive. In this project, the PC parallel port extension is used to emulate the microprocessor bus activity in read/write operation. The results showed an impressive students' progress whereas they were so satisfied to not only their projects, but also the conceptual basics of this course. © 2014 Wiley Periodicals, Inc. Comput Appl Eng Educ 23:455–463, 2015; View this article online at wileyonlinelibrary.com/journal/cae; DOI 10.1002/cae.21616